A study on socio-cultural factors and reproductive health of women with HIV/AIDS, in a tertiary care hospital, Kakinada, East Godavari district, Andhra Pradesh - Sowmyasudha, K.; Noor, Sofia; Tej, Alpha V. P.; Satyanarayana, K. (International Journal Of Community Medicine And Public Health, 2018)
Background: AIDS is a fatal disease caused by Human Immune-Deficiency Virus. Transmitted by sexual contact mainly heterosexuals, street children, adolescents, migrants are also major vulnerable group to affect. Social and cultural factors have a key role in transmission of the disease. Methods: A total of 303 positive HIV women in reproductive age group were interviewed to assess the socio-cultural factors and reproductive health among them, by using a semi-structured questionnaire. Data was analyzed by using SPSS software. Results: Un-educated and un-employed women from nuclear family with early marriage, having predisposing factors of alcoholism, polygamous sexual relationship were affected in this study. Few of them still have sexual relations, majority of them not disclosing their disease status. Few of them facing social stigma and lacking of family support. Majority has access to treatment and they are on regular treatment. Their antenatal and post natal period is un-eventful. A few of them stopped breastfeeding to their babies. Majority have one or two children affected by disease in their family. Conclusions: In our study we found the Major predisposing factor for the disease are STDs, alcoholism and major route of transmission is through sexual contact. A few participants have extramarital polygamous relationship and maintaining confidentiality on their disease status. Majority were on regular treatment. Most of them were not practicing family planning methods.